Konstruksi Upaya Guru Dalam Membangun Character Building Islami Melalui Perspektif Neurosains Dalam Pendidikan Agama Islam - Etika Pujianti (At-Ta'dib, 2024)
Indeed, the construction of education carried out by a teacher is an effort to build individual students to obey and obey the provisions of the prevailing values and norms. Moreover, the rules and procedures of education order will appear to be successful if students or learners have good skills and character. And this research wants to see how an educational construction is pursued by teachers in building religious character based on neuroscience education in Islamic religious education. By using case study research studies on in-depth material in the context of structured interviews to extract information and studies from religious education teachers and students. Displey data, data reduction and data verification are the data analysis methods used in this study. With the scope of the results that a building pursued by PAI teachers in this study is that the development of religious student characters based on neuroscience abilities in instilling love for God (Allah Swt) and Rosul Muhammad Saw. The efforts of Islamic religious education teachers are to teach, explain and define how humans as a whole should understand the importance of a pious character education value and provide peace / tasamuh to the soul and social. The teacher in this case, besides teaching and explaining, there is an effort to demonstrate the application of these values. So that teachers can become role models or in terms of role models and good role models. Teachers' efforts to build and realise students or learners with emotional awareness and skills in their efforts to handle emotions, emotional management, stress management and encourage with various motivations to students. So that such efforts and steps can be felt deeply by students/ learners. So that learners or students can optimally maximise their abilities and skills and intelligence that stems from the brain network system (neuroscience). And this effort aims to shape the construction of students' abilities to be able to adapt optimally in various social conditions and have implications for their role as the development of human beings with maximum thinking power and Islam.